Nuclear Magnetic Resonance in Tire Waste Mortars - Marta Ioana Moldoveanu; Daniela Lucia Manea; Elena Jumate; Raluca Iștoan; Radu Fechete; Tudor Panfil Toader (Applied Sciences)
This study aims to investigate the application of nuclear magnetic resonance (NMR) to characterize mortars containing recycled rubber waste as an eco-innovative material for sustainable construction. The primary objective was to analyze the way rubber granules influence hydration kinetics, microstructural development and pore structure. The innovative mortar formulations incorporated rubber granules, casein, natural hydraulic lime (NHL), and latex. NMR analysis revealed distinct T2 relaxation time distributions correlated with different pore sizes and water states: shorter T2 values demonstrate strongly bound water in small pores, while longer T2 values are associated with loosely bound or free water in larger pores. The formulation with 3.5% NHL and 5% rubber granules exhibited optimal microstructural characteristics. These results reveal that NMR is a valuable, non-destructive tool for monitoring cementitious material evolution and supporting the use of tire-derived waste in eco-innovative mortar designs.